ANALISIS POLA PEMASARAN PRODUK HNI-HPAI DALAM MENINGKATKAN JUMLAH PENJUALAN DILIHAT DARI PERSPEKTIF BISNIS SYARIAH - Khairunnisa, Viona; Dewi, Sandra (LPPM - STIE SAKTI ALAM KERINCI, 2024)
This thesis was prepared by Viona Khairunnisa NIM 3720037, Bachelor's Department of Sharia Business Management, Faculty of Economics and Islamic Business, UIN Sjech M. Djamil Djambek Bukittinggi with the title